Preliminary results on deconfinement phase transition in full QCD - S, Chagdaa; E, Galsandorj; B, Purev; O, Kaczmarek; H. T., Ding (Scientific transaction of the National University of Mongolia. Physics, 2022)
We explore the profiles of the flux tube connecting a quark and an antiquark in high temperature SU(3) lattice gauge theory in close vicinity to the critical temperature of the phase transition. In this work, we consider the more realistic case of the flux tube with dynamical quarks, extending the previous study to SU(3) gauge group and making use of the Gradient flow method in smoothing procedure for noise reduction. The profiles of the chromoelectric and chromomagnetic field strengths in the flux tube have been measured from Polyakov loop-plaquette correlations using the highly improved staggered quark (HISQ) action on a lattice with temporal extent.